Comparison of MTA, CEM Cement, and Biodentine as Coronal Plug during Internal Bleaching: An In Vitro Study - Paridokht Zarean; Parichehr Zarean; Arash Ravaghi; Maryam Zare Jahromi; Mitra Sadrameli (Hindawi Limited, 2020)
Background. Internal bleaching is a choice of treatment in discolored endodontically treated teeth. Cervical root resorption is one of the important complications of this treatment. A suggested procedure to prevent this type of resorption is using a coronal barrier under the bleaching materials. The aim of the study was to compare the microleakage of mineral trioxide aggregate (MTA), calcium-enriched mixture (CEM) cement, and Biodentine. Materials and Methods. In this in vitro study, a total of 60 single canal incisors were included. They were randomly divided into three experimental groups (n = 16), one positive control group (n = 6), and one negative control group (n = 6). Coronal portion of the canals in the experimental groups was sealed with 3 mm of MTA, CEM cement, or Biodentine as a coronal barrier. After 3 days, specimens were bleached. A fresh Enterococcus faecalis suspension was added to the samples. The culture tubes were observed for 45 days, and the daily turbidity was recorded. Statistical analysis was accomplished by the Kaplan-Meier test and SPSS 22. Results. All positive samples showed turbidity, whereas none of the negative samples allowed bacterial leakage. Results showed no significant difference between MTA, CEM cement, and Biodentine groups. (P value = 0.304, 0.695, and 0.217). The bacterial microleakage for the two groups also did not show significant differences. Conclusions. CEM cement and Biodentine showed promising results as coronal plug, and clinical studies are needed to test these materials with MTA for avoiding microleakage in internal bleaching treatment.